2015
DOI: 10.1063/1.4908121
|View full text |Cite
|
Sign up to set email alerts
|

Non-uniform depth distributions of Sn concentration induced by Sn migration and desorption during GeSnSi layer formation

Abstract: The distributions of Sn concentration in GeSnSi layers formed on Ge substrate at various temperatures were investigated. High deposition temperature (Td) induces significant Sn migration and desorption, which have activation energies of 0.65 eV and 0.27 eV, respectively. A model quantitatively clarified the Sn migration fluxes during the deposition, which increase not only with increasing Td but also with the layer thickness. A non-negligible Sn flux compared with the supplied flux was found at 350 C at the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Sn segregation during the growth and post-processing is one of the problems associated with the formation of homogeneous Ge 1− x Sn x layers. We found that Sn segregation occurs during the epitaxial growth of Ge 1− x − y Si x Sn y ternary alloys [20]. Sn segregation also occurs during the oxidation of Ge 1− x Sn x layers.…”
Section: Crystal Growth and Crystalline Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sn segregation during the growth and post-processing is one of the problems associated with the formation of homogeneous Ge 1− x Sn x layers. We found that Sn segregation occurs during the epitaxial growth of Ge 1− x − y Si x Sn y ternary alloys [20]. Sn segregation also occurs during the oxidation of Ge 1− x Sn x layers.…”
Section: Crystal Growth and Crystalline Propertiesmentioning
confidence: 99%
“…Therefore, Sn atoms often precipitate in a GeSn(Si) layer and segregate on a GeSn(Si) surface during deposition and annealing after GeSn(Si) layer formation (referred to as PDA) [20, 21, 94]. Furthermore, high deposition temperatures and PDA at high temperatures induce Sn desorption from the surface [20, 21, 95]. These results mean that MOS technology for an Sn-based alloy is a challenging technology because a technique to precisely control the physical behaviors of Sn atoms during layer formation and PDA must be established.…”
Section: Heterostructures Interfaces and Defect Propertiesmentioning
confidence: 99%
“…We note that the Sn content of the middle barrier layer does not seem to drop significantly from its value in the well layers. A possible explanation is that although growth temperatures were kept low, some Sn diffusion could have smeared out the transition region between barrier and well layers [18]. XRD analysis with PANalytical Empyrean was used to characterize both samples.…”
Section: Layer Growth and Characterizationmentioning
confidence: 99%
“…One of the serious problems is the Sn inclusion (precipitates) formation during GeSn layer growth [ 10 , 11 ]. In addition to precipitation, Sn segregation is observed in the process of GeSn, GeSiSn layer growth, and GeSn film oxidation [ 11 , 12 ]. Non-equilibrium growth techniques, such as the molecular beam epitaxy (MBE) and chemical vapor deposition (CVD), serve reliable methods of the precipitation and segregation suppression.…”
Section: Introductionmentioning
confidence: 99%